A Case of Comorbid PTSD and Posttraumatic OCD Treated with Sertraline-Aripiprazole Augmentation - Rodolfo Rossi; Cinzia Niolu; Alberto Siracusano; Alessandro Rossi; Giorgio Di Lorenzo (Case Reports in Psychiatry)
Several studies report on traumatic history in Obsessive Compulsive Disorder (OCD) and comorbidity between Posttraumatic Stress Disorder (PTSD) and OCD. First-line pharmacological treatments for both OCD and PTSD are primarily based on antidepressants, including Selective Serotonin Reuptake Inhibitors (SSRIs) and Serotonin-Noradrenaline Reuptake Inhibitors (SNRI) such as Venlafaxine for PTSD. Second-Generation Antipsychotic (SGA) augmentation has shown good outcomes for nonresponsive OCD cases. However, evidence on the use of SGA in PTSD is more limited. In the present paper, we report on comorbid OCD-PTSD successfully treated with aripiprazole augmentation of sertraline. Shared psychopathological and pharmacological aspects of the disorders are discussed.